Proxima Centauri b: infrared detectability in presence of stellar activity. (May 2020) - Galuzzo, D; Berrilli, F; Giovannelli, L
Abstract: We propose a general method to detect and characterize tidally-locked exoplanets in 1:1 spin/orbit resonance using the information coming from different infrared bands, analyzing the variation in time of the color of exoplanetary systems. We focus on the effects induced on the detectability of the system by the starspots of the active host-stars. The analysis is conducted on the Proxima Centauri system as a case study, comparing the results from a more complex 3D General Circulation Model simulation with a simple toy model. Our toy model includes the black-body emission in the infrared of the host-star, day-side and night-side of the tidally locked planet, as well as the starspots. The results are consistent with the 3D General Circulation Model and suggests that it is possible to disentangle the stellar activity effects from the presence of the planet in the exoplanetary system using the infrared color-color diagram technique.